2017
DOI: 10.1007/s11605-017-3470-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laparoscopy Prior to Neoadjuvant Therapy in Pancreatic Cancer Is High Yield: an Analysis of Outcomes and Costs

Abstract: SDL prior to NAT is a useful adjunct to CT to diagnose occult metastatic disease in BRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…A small percentage of patients will never make it to the operating room, often because of a combination of drainage-related complications (eg, cholangitis or pancreatitis) and frailty. Moreover, about 20% of radiographically BRPC patients will never undergo resection because of occult metastatic disease at staging laparoscopy or unexpected LAPC during surgical exploration (61,62). Finally, most adjuvant trials require a complete macroscopic resection, a CA 19-9 level below 180 U/ mL, and full recovery from surgery within 12 weeks after resection.…”
Section: Resection and R0 Resection Ratesmentioning
confidence: 99%
“…A small percentage of patients will never make it to the operating room, often because of a combination of drainage-related complications (eg, cholangitis or pancreatitis) and frailty. Moreover, about 20% of radiographically BRPC patients will never undergo resection because of occult metastatic disease at staging laparoscopy or unexpected LAPC during surgical exploration (61,62). Finally, most adjuvant trials require a complete macroscopic resection, a CA 19-9 level below 180 U/ mL, and full recovery from surgery within 12 weeks after resection.…”
Section: Resection and R0 Resection Ratesmentioning
confidence: 99%
“…Tumor size and increased carbohydrate antigen 19‐9 (CA 19‐9) values have been previously associated with OMD . Diagnostic laparoscopy is routinely utilized in certain institutions for the assessment of possible disseminated abdominal disease and prevention of unnecessary laparotomy . However, utilization of diagnostic laparoscopy in all patients is time‐consuming and costly, especially due to the limited sensitivity in identifying small metastases in the posterior liver surface and the visceral peritoneum of the small bowel …”
Section: Introductionmentioning
confidence: 99%
“…5,[10][11][12][13] Diagnostic laparoscopy is routinely utilized in certain institutions for the assessment of possible disseminated abdominal disease and prevention of unnecessary laparotomy. 14,15 However, utilization of diagnostic laparoscopy in all patients is timeconsuming and costly, especially due to the limited sensitivity in identifying small metastases in the posterior liver surface and the visceral peritoneum of the small bowel. 16 We retrospectively reviewed all explored patients with radiographically resectable PDAC within the past 10 years, to address an important question for patient care: what are the contemporary incidence and the associated risk factors for OMD.…”
Section: Introductionmentioning
confidence: 99%
“…There are still a number of cases that were determined to be non-resectable after staging laparoscopy, particularly in borderline resectable cases. Peng et al [37] found that still up to 25% of cases were found to be non-resectable in borderline resectable cases. The reason for including both resectable and borderline resectable cases in our study was to demonstrate the increased yield for staging laparoscopy especially in borderline resectable cases.…”
Section: Limitationsmentioning
confidence: 99%